Chapter Introductory Essay Shaping Interdisciplinary and Transdisciplinary Research - Vienni Baptista, Bianca (Bristol University Press, 2023)
Introduction essay and Chapter 1 are available Open Access under CC-BY-NC-ND licence. This groundbreaking reader is designed to lower the barriers to interdisciplinarity and transdisciplinarity in research. Edited by experienced researchers from a range of different fields, it paves the way for future scholarship and effective research collaborations across disciplines. Chapters offer extracts from key academic texts on topics such as the design, funding, evaluation and communication of research, providing those new to the field with a thorough grounding. They highlight examples of interdisciplinary and transdisciplinary triumphs - and challenges. Concluding each chapter is a commentary provided by practitioners from diverse backgrounds, many of whom are themselves developing new approaches to inter- and transdisciplinarity. The book is: • the first ever comprehensive reader for interdisciplinarity and transdisciplinarity; • essential reading for those seeking to become effective collaborative researchers; • complete with concise introductions, extracts, commentary and further reading in each chapter. This is a much-needed primer that improves our understanding of the characteristics of interdisciplinarity and transdisciplinarity, unlocking their exciting potential in research and teaching within and beyond academia.